"Klasyczna socjologia" w lokalnych opowieściach = "Classical sociology" in local narratives - Kilias, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author deals with the history of works concerning the history of classical sociology written by Czech and Polish scholars. He stresses that in most cases these were not written by historians but rather by theorists, who sometimes lacked any serious interest in the history of the discipline and who rarely showed any historical methodological awareness.
Keywords: socjologia; socjologia klasyczna; Polska; Czechy